FINANCIAL EDUCATION FOR CHILDREN IN GONGSOL VILLAGE: INSTILLING THE IMPORTANCE OF SAVING EARLY - Ayu, Aisah Citra; Afandi, Ahmad (Antis-publisher, 2024)
General Background: Financial literacy is essential for developing responsible financial behaviors, particularly when introduced at an early age. Specific Background: In Gongsol Village, financial education programs targeting children aim to instill the importance of saving and financial management from a young age. Knowledge Gap: However, financial literacy initiatives specifically designed for children in rural communities remain limited, and their long-term effectiveness has not been thoroughly explored. Aims: This study evaluates the implementation of a financial education program that focuses on basic financial concepts, such as the distinction between needs and wants, managing pocket money, and saving practices. Results: The program engaged children through interactive educational activities, with 100% of participants expressing a clear understanding of the materials and a desire to continue their financial education. Additionally, the children demonstrated improved awareness of the value of saving and financial planning. Novelty: This program highlights a tailored approach to rural financial education, effectively bridging the gap in early financial literacy initiatives in underserved areas. Implications: The program’s success indicates the potential for similar interventions in other rural areas, promoting financial discipline and preparing future generations to face economic challenges with greater competence. Further research could explore the long-term impact of such education on financial behavior.